Kinetics and Mechanism of the Thermal Decomposition of o-Vanillin-L-Histidine Complexes of Transition Metal Ions - Sleema, B.; Parameswaran, Geetha (Asian Journal of Chemistry, 2010)
0-Vanillin-L-histidine forms 1 : 1 complexes with the transition metals like manganese, cobalt, nickel, copper and zinc. All the complexes are found to be non-electrolytes in distilled water and octahedral structures are assigned to them based on electronic, ESR and room-temperature magnetic measurements. IR studies reveal that the o-vanillin-L-histidine can act as a tridentate ligand towards the transition metals. The thermal decomposition of Mn(ll), Co(ll). Ni(ll), Cu(ll) and Zn(ll) chelates of o-vanillin-L-histidine was studied by thermogravimetry. Thermal studies indicate that the decomposition takes place in two stages. The kinetic parameters, namely activation energy E. pre-exponential factor A and entropy of activation λS were also calculated from the thermogravimetric curves using mechanistic and non-mechanistic (Coats-Redfern) equations. The inechanism of the decomposition has been established from thermogravimetric data. On the basis of nur findings the relative thermal stabilities of the chelates can be given as [CoL(H2O)3] ≈ [CuL(H2O)3] < [ZnL(H2O)3] ] < [MnL(H2O)3] < [NiL(H2O)3]·